(untitled) (Al-Mansour Journal, 2026)
The current paper aims to investigate the global latest movement of developing human resource management systems in parallel with the rapid transferring into the adoption of artificial intelligence in all aspects of life i.e., healthcare, education systems, business processes, logistic chain processes…etc. Since Arabian region presents around (10.2%) of the world in two continents and its papulation around (5%) of total global population which leads it to compete towards change and develop as others, so, this paper could be a good guide to perform a review of the scientific articles in Arabian libraries that related to the same terms of artificial intelligence and human resource management for the last two decades to understand the current and the coming steps that should follow artificial intelligence recently has its impact of the field of human resource management with gently growth towards positive future horizon that represented by human resource analytics. The objective of this article is to scan academic works systematically and trying to submit a comprehensive vision of the future of artificial intelligence usages in human resource management in Arabian Region.